A fábula do telejornal: estudo das imagens e da estrutura narrativa da reportagem no telejornal em sua aproximação com o gênero fábula - Lima, Jefferson Alves de (2010)
The observation of the presence of elements of narrative fiction in television news represents the central aspect of this study. Recognized for authors as Elizabeth Bird and Robert Dardene, Paul Weaver, François Jost, Robert Stam and Iluska Coutinho, this strange presence of the attributes of fiction in television news is examined here specially as a basis to build the main unit of the program: the reportage. Before the speech space self-assumed by the television news as a reference for society, we observe an established relationship between the program and the ability of narrative fiction for representing and orienting social values. We examine in this study the approximation of the visual plots, which are converted the news in television, with the orientation of behaviors and contours of life in society that the stories sediment throughout centuries . More specifically, we will examine the approximation of television news reportages with the fables, like Indians Pañcatantras or stories of the grecian Esopo. As a theoretical contribution for this observation, we start from authors of reference and deepen the studies on the televisions areas, journalism, TV journalism and narrative. By analysis of national televisions news Jornal Nacional, of the Rede Globo de Televisão, and Jornal da Cultura, of the TV Cultura, we identify the relation of the television news service with the fables